Adaptation and Use of a Five-Task Model for Evaluability Assessment - Brad R. Watts; Heather M. Washington (Journal of MultiDisciplinary Evaluation)
Background: Over four decades have passed since the concept of evaluability was introduced; however, the availability and accessibility of methodology, frameworks, checklists and other guidance on evaluability assessments remains limited (Smith, 2005). Evaluators who wish to conduct an evaluability assessment must adopt one of few existing models or operate without guidance. This case provides an example of one model and how it was utilized to conduct an evaluability assessment of an ongoing program intervention.